2006
DOI: 10.1542/peds.2005-3024
|View full text |Cite
|
Sign up to set email alerts
|

Emotional, Behavioral, Social, and Academic Outcomes in Adolescents Born With Very Low Birth Weight

Abstract: From parents' point of view, significant proportions of very low birth weight adolescents experience more emotional and behavioral problems and less competence than normative adolescents. In contrast, very low birth weight adolescents state less problems and similar or higher competence than normative adolescents. Very low birth weight adolescent girls report more emotional and behavioral problems compared with their parents than very low birth weight adolescent boys do. Externalizing problems in very low birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
119
3
7

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(147 citation statements)
references
References 58 publications
18
119
3
7
Order By: Relevance
“…In relation to cognitive performance and behavioral problem, in agreement with the literature (Dahl et al, 2006;Samara et al, 2008;Verdehus et al, 2015), we observed a significant relationship between these variables and quality of life. Behavioral problems, however, were maintained as risk factor for quality of life in the final regression.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In relation to cognitive performance and behavioral problem, in agreement with the literature (Dahl et al, 2006;Samara et al, 2008;Verdehus et al, 2015), we observed a significant relationship between these variables and quality of life. Behavioral problems, however, were maintained as risk factor for quality of life in the final regression.…”
Section: Resultssupporting
confidence: 92%
“…According to Johnston e Hagberg (2007), reasons that behavior disorders are more common in male individuals are not clearly defined, but evidence suggests that prematurely born males have cerebral white matter, which is more vulnerable to injuries and ventricular hemorrhages. According to Dahl et al (2006), in addition to biologic aspects, parents seem to present more difficulty detecting behavior problem in girls, which compromises the comparison with boys.…”
Section: Resultsmentioning
confidence: 99%
“…Pelos dois critérios de estratificação da coorte, os dados obtidos são concordantes com os dados da literatura que apontam para a vulnerabilidade desses grupos (Aarnoudse-Moens et al, 2009;Bhutta et al, 2002;Dahl et al, 2006;Martins et al, 2005;Msall & Park, 2008;Oliveira et al, 2011). Constatou-se ainda, que as crianças nascidas com baixo peso apresentaram mais dificuldades na escala de sintomas emocionais em comparação aos nascidos com peso normal, mas não apresentaram mais problemas comportamentais avaliados pelo escore total, enquanto as crianças nascidas PIG apresentaram mais sintomas emocionais e também mais dificuldades quanto ao escore total em comparação às nascidas AIG.…”
Section: Discussionunclassified
“…Em relação às crianças nascidas PIG, alguns estudos apontaram que essas crianças não apresentam mais problemas internalizantes (Dahl et al, 2006;Hack et al, 2004), diferentemente do observado no presente estudo, o que evidencia a importância de explicitar os aspectos combinados quando da comparação de resultados. No estudo de Dahl et al (2006) predominou o grupo de crianças nascidas com muito baixo peso, enquanto no presente estudo apenas 3% das incluídas eram nascidas nessa faixa de peso, predominando o baixo peso.…”
Section: Discussionunclassified
See 1 more Smart Citation